2013
DOI: 10.1159/000356253
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal Transvesical Laparoscopic Repair of Vesicovaginal Fistulae: Experience of a Tertiary Care Centre in Northern India

Abstract: Objective: To present our experience of treating supratrigonal vesicovaginal fistulae by laparoscopic technique and their long-term follow-up. Material and Methods: Between January 2008 and June 2012, 28 cases of supratrigonal fistulas were repaired by laparoscopic transperitoneal transvesical technique with interposition flap. The obstetric fistula was present in 18 and gynecologic fistula in 10 patients. Single supratrigonal fistula was present in 26 patients and in 2 patients there were 2 fistulae lying sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…It was reported that blood loss in robotic surgery was significantly less compared to open surgery (88 vs. 170 mL) [17,19]. In addition, it was reported that blood loss ranges from 50 mL to 125 mL in various laparoscopic repair cases [18]. There was no notable blood loss in our cases.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It was reported that blood loss in robotic surgery was significantly less compared to open surgery (88 vs. 170 mL) [17,19]. In addition, it was reported that blood loss ranges from 50 mL to 125 mL in various laparoscopic repair cases [18]. There was no notable blood loss in our cases.…”
Section: Discussionmentioning
confidence: 46%
“…In most cases, laparoscopic management of VVFs takes a relatively long time. The mean operative time in the literature ranges from 70 to 280 minutes in laparoscopic repairs and from 110 to 330 minutes in robot-assisted laparoscopic repairs [16][17][18]. The mean operative time in our study is 41 minutes.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although minimally invasive surgery (MIS) such as laparoscopy and robotics is more accessible in high-income countries (HIC), a group in India is utilizing MIS to repair urogenital fistulae resulting from obstetric complications [ 28 ]. This group reportedly closed vesicovaginal fistulae with a single layer continuous laparoscopic suture with interposition of an omental flap; urethral catheters were left in situ for a month post-operatively [ 28 ]. As the capacity for MIS in LIC builds, it will be interesting to see how this experience contributes to the surgical literature.…”
Section: Diagnosis Treatment and Managementmentioning
confidence: 99%